Beholding Beauty : Saʿdi of Shiraz and the Aesthetics of Desire in Medieval Persian Poetry - Ingenito, Domenico (Brill Studies in Middle Eastern Literatures, 2020)
Beholding Beauty: Saʿdi of Shiraz and the Aesthetics of Desire in Medieval Persian Poetry explores the relationship between sexuality, politics, and spirituality in the lyrics of Saʿdi Shirazi (d. 1292 CE), one of the most revered masters of classical Persian literature. Relying on a variety of sources, including unstudied manuscripts, Domenico Ingenito presents the so-called "inimitable smoothness" of Saʿdi's lyric style as a serene yet multifaceted window into the uncanny beauty of the world, the human body, and the realm of the unseen. The book constitutes the first attempt to study Sa'di's lyric meditations on beauty in the context of the major artistic, scientific and intellectual trends of his time. By charting unexplored connections between Islamic philosophy and mysticism, obscene verses and courtly ideals of love, Ingenito approaches Sa'di's literary genius from the perspective of sacred homoeroticism and the psychology of performative lyricism in their historical context.